2020
DOI: 10.3390/jof6030100
|View full text |Cite
|
Sign up to set email alerts
|

Lipid Species in the GI Tract are Increased by the Commensal Fungus Candida albicans and Decrease the Virulence of Clostridioides difficile

Abstract: Prior antibiotic treatment is a risk factor for Clostridioides difficile infection (CDI); the commensal gut microbiota plays a key role in determining host susceptibility to the disease. Previous studies demonstrate that the pre-colonization of mice with a commensal fungus, Candida albicans, protects against a lethal challenge with C. difficile spores. The results reported here demonstrate that the cecum contents of antibiotic-treated mice with C. albicans colonization contained different levels of sev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 84 publications
0
9
0
Order By: Relevance
“…Total levels of bacteria were measured using qPCR and universal 16S rRNA primers as previously described ( 60 ). Relative abundance was multiplied by the total level of bacteria per milligram of cecum sample ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Total levels of bacteria were measured using qPCR and universal 16S rRNA primers as previously described ( 60 ). Relative abundance was multiplied by the total level of bacteria per milligram of cecum sample ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…While the contributions of commensal fungi during bacterial infections are not well understood, fungi have been implicated in a variety of polymicrobial interactions that could significantly impact host health ( 9 , 55 , 80 - 83 ) including those involving CDI ( 15 , 24 , 25 , 28 , 29 , 60 , 84 - 86 ). More recently, Santus and co-workers showed that Salmonella enterica can utilize commensal and dietary fungal siderophores which promote Salmonella colonization ( 87 ).…”
Section: Discussionmentioning
confidence: 99%
“…As a novel microbe colonizing the GI tract, C. albicans could have affected the bacterial microbiota through multiple physiological pathways. Previous researchers have characterized multiple changes in the immune environment of the gut in response to C. albicans colonization ( 35 , 36 ), and Romo et al demonstrated that C. albicans alters the metabolite milieu of the gut through increased abundance of nonesterified unsaturated fatty acids and other lipid species ( 37 ). In sum, our study adds to the body of work demonstrating that C. albicans , a fungus, mildly alters the composition of the bacterial microbiota in the context of the mouse GI tract environment.…”
Section: Resultsmentioning
confidence: 99%
“…Another study found that the presence of C. albicans altered the levels of several lipid species in the mouse cecum, including non-esterified, unsaturated long-chain fatty acids. 83 Clearly, more comprehensive metabolome studies, ideally carried out in gnotobiotic animals, are needed to start delineating the metabolic footprint of the fungus in the intestine.…”
Section: Metabolic Niche Occupied By C Albicans In the Intestinementioning
confidence: 99%